2020
DOI: 10.1177/1468087420946551
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of diesel spray–assisted dual-fuel ignition: A comparative study on two n-dodecane mechanisms at different ambient temperatures

Abstract: In dual-fuel compression ignition engines, a high-reactivity fuel, such as diesel, is directly injected to the engine cylinder to ignite a mixture of low-reactivity fuel and air. This study targets improving the general understanding on the dual-fuel ignition phenomenon using zero-dimensional homogeneous reactor studies and three-dimensional large eddy simulation together with finite-rate chemistry. Using the large eddy simulation framework, n-dodecane liquid spray is injected into the lean ambient methane–air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 53 publications
4
24
1
Order By: Relevance
“…A skeletal chemical mechanism (54 species and 269 reactions) developed by Yao et al [30] for n-dodecane combustion is used. The performance of this mechanism in DF context has been already demonstrated in our earlier studies [25,34,36].…”
Section: D Reacting Shear Layersupporting
confidence: 56%
See 2 more Smart Citations
“…A skeletal chemical mechanism (54 species and 269 reactions) developed by Yao et al [30] for n-dodecane combustion is used. The performance of this mechanism in DF context has been already demonstrated in our earlier studies [25,34,36].…”
Section: D Reacting Shear Layersupporting
confidence: 56%
“…The n-dodecane jet is initially set to 700 K whereas the methane/air mixture is set to 900 K at a constant pressure of 60 bar. The initial conditions corresponding to the ambient premixed mixture are similar to our previous DF spray studies [25,[33][34][35][36][37] as reported in Table 2. The n-dodecane jet moves initially with a relative ve-locity of 10 m/s to the methane/air stream and develops a Kelvin-Helmholtz instability.…”
Section: D Reacting Shear Layermentioning
confidence: 86%
See 1 more Smart Citation
“…The n-dodecane jet is initially set to 700 K whereas the methane/air mixture is set to 900 K at a constant pressure of 60 bar. The initial conditions corresponding to the ambient premixed mixture are similar to our previous DF spray studies 33,[43][44][45][46][47] as reported in Table II. The n-dodecane jet moves initially with a relative velocity of 10 m/s to the methane/air stream and develops a Kelvin-Helmholtz instability.…”
Section: B 2d Reacting Shear Layermentioning
confidence: 92%
“…The performance of this mechanism in DF context has been already demonstrated in our earlier studies. 33,44,46 Figure 5 highlights the DF ignition process in the shear layer, where the n-dodecane jet ignites the surrounding mixture. It is observed that the first-stage ignition from low-temperature chemistry develops primarily within the n-dodecane jet near the mixing layer.…”
Section: B 2d Reacting Shear Layermentioning
confidence: 99%